Banishing "Siberia" and Student Seclusion: Leading Trauma-Informed Systems Change in a Rural School. (June 2020) - Biddle, Catharine; Brown, Lyn Mikel
Trauma-informed school practices require enactment of trauma-informed principles including prioritizing students' physical and psychological safety, connection, cultural responsiveness, and student empowerment. These principles frequently challenge teachers' preexisting beliefs about rules, consequences, and the intention behind student behaviors. In this case, an early career principal must address the actions of several teachers who chose to reinstate a previously existing seclusion room that had been transformed into a food pantry. The case highlights issues in supporting staff divided around school change, being an early career school leader in a rural school with high leadership turnover, and managing relationships between staff and external school partners.